(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
This paper gives an account of the first results of a series of Portian investigations, prompted by the discovery of part of Giovanni Antonio Maggi’s manuscript papers. In particular, the investigation starts from the documentary evidence that the ’Lament del Marchionn di gamb avert’ was already circulating at the end of June 1816, even if in a form still far from that assumed in its first edition.